Remarkable Acid Stability of Polypyrrole‐MoS4: A Highly Selective and Efficient Scavenger of Heavy Metals Over a Wide pH Range. (30th March 2018) - Xie, Linxia; Yu, Zihuan; Islam, Saiful M.; Shi, Keren; Cheng, Yahan; Yuan, Mengwei; Zhao, Jing; Sun, Genban; Li, Huifeng; Ma, Shulan; Kanatzidis, Mercouri G.
Abstract: The new material polypyrrole/MoS4 2− (MoS4 ‐Ppy), prepared by ion‐exchange of NO3 ‐ of NO3 ‐Ppy with MoS4 2−, displays high acid stability and excellent uptake for heavy metal ions such as Hg 2+, Ag +, Cu 2+, and Pb 2+ . The different maximum adsorption capacities ( q m ) for Cu 2+, Pb 2+, Hg 2+, and Ag + depend on the various binding modes arising from the different thiophilicity of these metal ions. The removals of Ag + and Pb 2+ reach >99.6% within 5 min, and for highly toxic Hg 2+, >98% removal achieves at 1 min. At strong acid limit, the exceptional q m (Ag + ) of 725 mg g −1 places the MoS4 ‐Ppy at the top of materials for such removal. Uptake kinetics of Ag +, Hg 2+, and Pb 2+ is extremely fast: >99.9% removal rates at wide pH range (0.5–6) within 1–5 min. Also, at strongly acidic conditions (pH ≈ 1), for highly toxic Hg 2+, <2 ppb concentration can be achieved, accepted as safe limit. The MoS4 ‐Ppy demonstrates an outstanding ability to separate low‐concentrated Ag + from high concentrated Cu 2+ especially under strong acidic conditions (pH ≈ 1), showing a large separation factor SFAg/Cu ( K d Ag / K d Cu ) of 10 5 (>100). MoS4 ‐Ppy is a superior and novel sorbent material for water remediation applications as well as precious metals recovery. Abstract : The new material of polypyrrole/MoS4 2− (MoS4 ‐Ppy) displays high acid stability and excellent uptake for heavy metal ions of Hg 2+, Ag +, Cu 2+, and Pb 2+ . High distribution coefficients (≈10 7 mL g −1 ), rapid kinetics (99% uptake within 1–5 min), and exceptionally large maximum capacity (such as 725 mg g −1 for Ag + ) especially at strong acidic condition place the MoS4 ‐Ppy at the top of materials.